Electronic Properties of the Zirconium Crystal with Vacancies and Dynamics of Vacancies: ab-initio Calculations and Molecular Dynamics - V.O. Kharchenko; S.V. Kokhan (Журнал нано- та електронної фізики)
Within this paper we have the studied structural and electronic properties of zirconium crystal with vacancies from the first principles. We have defined the optimal values for the lattice constants. The corresponding densities of states and energetic spectrum were calculated. These results gave a possibility to define the Fermi structure of the zirconium crystal with vacancies. In the framework of the molecular dynamics simulations we have studied the dynamics of the ensemble of periodically located vacancies in the zirconium crystal with an increase in temperature. We have analyzed the reconstruction of atomic structure and change in the total volume of the crystal with the temperature growth. The dependencies of the volume expansion coefficient for the pure zirconium without vacancies end zirconium crystal with different vacancies concentration on the temperature were studied.